Immunity indices in patients with atopic dermatitis with different polymorphisms in Glutathioni-S-Transferase genes - A. A. Kubanov; T. A. Sysoeva; Yu. A. Gallyamova; A. S. Bisharova; I. B. Mertsalova (Лечащий Врач, 2021)
Results of the genetic typing and immunologic analysis in patients with atopic dermatitis are presented. Various genetic polymorphisms in genes of GST (M1, T1 and P1) were described in patients with atopic dermatitis. The whole set of the results obtained indicates the necessity to pay attention to the detoxication abnormalities in patient with atopic dermatitis while working out personalized treatment and preventive measures.